Preferensi Petani terhadap Pembiayaan Syariah di Kabupaten Jember - Herman Cahyo Diartho; Rohmad Kurniawan; Zaenuri Zaenuri (P4W LPPM IPB, 2019)
Islamic financing system continues to evolve, which can be observed from the increase in the number of financial institutions that employ Islamic financing models from bank level to cooperative level. Islamic financial institutions were initially related to large industrial sector but then began to enter the field of agriculture, so it is necessary to conduct research on farmers’ preference on Islamic economic financing. This research has three objectives: to understand the significance influence of easiness factor, knowledge factor, and trust factor on farmers’ preference on Islamic financing. The method of SEM (Structural Equation Modeling) was used as a tool in order to solve problems in this research through calculation using of AMOS 21 application. Results of the research shows that there is only one factor that has significant effect on Islamic financing, which is the trust factor with a coefficient of 0.090. Meanwhile the knowledge factor and easiness factor has no significant effect